Formation of bovine serum albumin–galangin nanoparticles and their potential to inhibit reactive oxygen species–induced inflammation: Ethanol desolvation versus pH-shifting method - Weigang Zhong; Lei Xu; Qi Wang; Xue Shen (Journal of Dairy Science)
ABSTRACT: The pH-shifting method, as an ecofriendly approach, is a promising alternative to the desolvation method, yet systematic comparison of their properties is still lacking. In this study, BSA-galangin nanoparticles (BSA-GA NP) were designed for alleviating reactive oxygen species (ROS)–mediated macrophage inflammation by the 2 separate methods. Compared with the desolvation method, BSA exhibited a higher loading capacity for GA under the pH-shifting method, which was attributed to the exposure of the binding site leading to enhanced affinity for GA and a more compact particle structure. Further analyses evidenced that the electron arrangement and crystal structure of GA changed with different methods. The content of the random coil of BSA was elevated after the pH-shifting method. Additionally, the smaller size rendered the pH-shifting treated BSA-GA NP easier to be taken up by macrophages, and the enhanced specific surface area conferred excellent ROS scavenging and anti-inflammatory performances. This study may provide new insights into the choice of loading methods.